2014
DOI: 10.5942/jawwa.2014.106.0064
|View full text |Cite
|
Sign up to set email alerts
|

Importance of pipe deposits to Lead and Copper Rule compliance

Abstract: When Madison, Wis., exceeded the lead action level in 1992, residential and off‐line tests suggested that lead release into the water was more complex than a lead solubility mechanism. Scale analyses (color and texture as well as mineralogical and elemental composition) of five excavated lead service lines (LSLs) revealed that accumulation of manganese (and iron) onto pipe walls had implications for lead corrosion by providing a high‐capacity sink for lead. Manganese that accumulated from source well water ont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 60 publications
(68 citation statements)
references
References 42 publications
3
61
0
Order By: Relevance
“…It is currently believed that a very large reservoir of iron has accumulated on the lead pipes over the years, which might take a very long time to deplete even after iron stops accumulating. This creates a longer-term problem with lead particulate release, consistent with prior research on long-term problems associated with inorganic contaminant reservoirs in distribution systems (Reiber and Dostal, 2000;Lytle et al, 2004;Schock, 2005;Cantor, 2006;Deshommes et al, 2010;Lytle et al, 2010;Schock et al, 2014).…”
Section: Profile Samplingsupporting
confidence: 71%
See 1 more Smart Citation
“…It is currently believed that a very large reservoir of iron has accumulated on the lead pipes over the years, which might take a very long time to deplete even after iron stops accumulating. This creates a longer-term problem with lead particulate release, consistent with prior research on long-term problems associated with inorganic contaminant reservoirs in distribution systems (Reiber and Dostal, 2000;Lytle et al, 2004;Schock, 2005;Cantor, 2006;Deshommes et al, 2010;Lytle et al, 2010;Schock et al, 2014).…”
Section: Profile Samplingsupporting
confidence: 71%
“…Anecdotally, several studies have identified links between high levels of particulate lead and particulate iron in both natural and engineered systems, suggesting that mitigation of particulate lead problems might sometimes be associated with reducing other particulates present in the distribution system (Hulsmann, 1990;Erel et al, 1991;De Rosa and Williams, 1992;Erel and Morgan, 1992). More recent studies have elucidated more definitive links between elevated particulate lead and particulate iron in drinking water (HDR, 2009;Deshommes et al, 2010;Camara and Gagnon, 2012;Triantafyllidou and Edwards, 2012;Camara et al, 2013;Knowles et al, 2015;Schock et al, 2014). Given that more than a quarter of the distribution system in the United States is unlined iron (Baird, 2011), a better understanding of the potential link between lead and particulate iron is important.…”
Section: Introductionmentioning
confidence: 93%
“…The corrosion scales in this study were analyzed over the course of the past 25 years, using multiple analytical techniques that have previously been described in detail (DeSantis & Schock, ; DeSantis, Schock, & Bennett‐Stamper, ; DeSantis, Welch, & Schock, ; Schock et al, ; Schock & Lytle, ; Schock, Scheckel, DeSantis, & Gerke, ; Triantafyllidou, Schock, DeSantis, & White, ; Wasserstrom et al, ). Although there has been some variation in preanalysis sample handling and in analytical procedures available over the time study samples were collected, the general procedure was to ship the LSLs to the USEPA's AMSARC in Cincinnati for evaluation.…”
Section: Methodsmentioning
confidence: 99%
“…For example, studies have not conclusively determined the factors causing the specific formation of observed Pb(II) orthophosphate solids such as Pb 5 (PO 4 ) 3 OH (hydroxypyromorphite), Pb 5 (PO 4 ) 3 Cl (pyromorphite), or tertiary lead phosphates (Pb 3 (PO 4 ) 2 , Pb 9 (PO 4 ) 6 ) (Hopwood et al, ). Furthermore, studies (DeSantis & Schock, ; Hayes, Croft, Phillips, Craik, & Schock, ; Kim & Herrera, ; Schock, Cantor, Triantafyllidou, Desantis, & Scheckel, ; Snoeyink et al, ; Wasserstrom, Miller, Triantafyllidou, Desantis, & Schock, ) have noted the extensive presence of amorphous solid phases in a number of drinking water distribution systems (DWDSs). The conditions that govern when amorphous solid phases, rather than defined crystalline phases, form have not been systematically determined.…”
Section: Introductionmentioning
confidence: 99%
“…The pipe samples were cut longitudinally, photographed and then analyzed by PXRD for scale mineralogy of the water contact scale layer following procedures detailed elsewhere (Schock et al, 2014). The pipe samples were also analyzed by scanning electron microscopy with energy dispersive spectroscopy (SEM/EDS) for scale morphology.…”
Section: Solid Sample Analysesmentioning
confidence: 99%